SOME ASPECTS OF THE DEFINITION OF EMPTY CARS STABILITY FROM SQUEEZING THEIR LONGITUDINAL FORCES IN THE FREIGHT TRAIN - Shvets, A. O.; Zhelieznov, K. I.; Akulov, A. S.; Zabolotnyi, O. M.; Chabaniuk, E. V. (Science and Transport Progress, 2015)
Purpose. Despite of the implementation various programs to improve the safety of train traffic problem of reducing gatherings rolling stock off the rails is still relevant. The study aims to clarify the existing method of determining the factor of stability from the tire longitudinal forces to ensure the sustainability of cars with increasing speeds of the rolling stock. Methodology. Research was conducted by the method of mathematical modeling of loading freight car when driving at different speeds on straight and curved track sections. Findings. Analysis of the results shows that, for all selected freight cars for the calculation, the value of the safety factor by squeezing is smaller than the formulas of Standards. Corrections made to the formula for determining the safety factor by squeezing longitudinal forces, would achieve: 1) a higher safety factor of lightweight cars, excluding them squeezing longitudinal forces in the entire range of speeds of freight trains; 2) to develop and implement measures to prevent squeezing of cars in the entire range of motion; 3) to determine the degree of stability of the empty car in the head, middle and tail laden trains; 4) to offer optimal scheme of mixed trains formation. Originality. The analysis of existing methods for determining stability coefficient cars in freight trains from squeezing their longitudinal forces is presented in studies. Proposals are developed for the refinement of the design phase, construction and operation. Practical value. This study clarifies the existing method of determining the safety factor of stability from the squeezing longitudinal forces, as well as the influence on the magnitude of the coefficient of speed of movement of the rolling stock. Developed proposals for the refinement of existing methods for determining stability coefficient of longitudinal forces squeezing cars in a train, can reduce the number of retirements cars derailed by taking into account in the calculation and design of important parameters and characteristics that increase their stability in the rail track especially with increasing speeds of freight traffic.